JAMALUDDIN AL-AFGHANI'S EDUCATIONAL AND POLITICAL RENEWAL IDEAS - Kusumawati, Herlina Arum (Jurnal Kajian Pendidikan dan Psikologi, 2023)
The aim of this research is to examine in depth the figure of reform in both the fields of education and modern Islamic politics, Al-Afgani, whose discussion includes biography, career history, works, thinking, or educational development put forward by these figures. The author uses library research methods, namely research by collecting various books, scientific journals, theses, and other information that is used as a source of information. Result analysis explained that Jamaluddin Al Afghani is a popular Muslim figure in educational and political reform and represents a modernist-rationalist fashion group that is responsive to developing knowledge. Jammaluddin Al-Afghani There is a person known as a political activist or pessimistic PAN. Islamism aims to unite people in Islam and fight colonialism.